Risk Factors Analyses Correlating with Productive Age Population Coronary Heart Disease in Manado and Tomohon - A Natalino (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2017)
Background: Cardiovascular diseases remain the leading cause of death in the world relating .....